Characterization and Expression Analysis of PUB Gene Family Involved in Drought Stress Response in Trifoliate Orange (Poncirus trifoliata) - Bobo Song; Sanpeng Jin; Xuchen Gong; Yong Liu; Dechun Liu; Li Yang; Wei Hu; Liuqing Kuang; Jie Song (Horticulturae, 2025)
The U-box E3 ubiquitin ligase (PUB) gene family plays an important role in regulating plant responses to abiotic stress. Poncirus trifoliata (trifoliate orange), a citrus rootstock with notable cold, drought, and salt tolerance, serves as an excellent model for studying stress-responsive genes. In this study, a total of 47 PUB genes (PtrPUBs) were identified in the trifoliate orange genome. Chromosomal distribution analysis indicated that PtrPUB genes were unevenly distributed across nine trifoliate orange chromosomes. Phylogenetic tree analysis indicated that 170 PUB proteins from trifoliate orange, Arabidopsis thaliana, and tomato were clustered into five subfamilies. Gene structure, conserved domain, and motif analyses revealed diverse exon–intron and motif organizations of PtrPUB genes, suggesting potential functional differentiation among PtrPUBs. Cis-acting analysis indicated that the promoters of PtrPUB genes harbor elements related to hormone signaling (ABA, MeJA), drought stress, and low-temperature responses. Transcriptomic data and qRT-PCR results suggested that PtrPUB genes are responsive to ABA and dehydration treatments. This study provides a foundation for understanding the functional roles of PUB genes in trifoliate orange and offers insights for improving stress tolerance in citrus breeding programs.